La cibernetica prima della cibernetica. Filosofia, scienza e tecnica in Norbert Wiener (1914-1943) - Ferrari, Marco (Philosophy Kitchen - Rivista di filosofia contemporanea, 2023)
The paper provides a survey of Norbert Wiener’s scientific work prior to the publication of Cybernetics. Within it, an attempt is made to identify the philosophical-scientific background of cybernetics and to reconstruct the generative process of its main concepts. In conclusion, on the basis of this inquiry, a novel definition of “what we talk about when we talk about cybernetics” is proposed and, on this basis, opens up the need for its critical questioning by philosophy.